Fabrication of K2O–Al2O3–Gd2O3–P2O5 glasses for photonic and scintillation materials applications. (November 2021) - Kiwsakunkran, N.; Chaiphaksa, W.; Chanthima, N.; Kim, H.J.; Kothan, S.; Prasatkhetragarn, A.; Kaewkhao, J.
Abstract: Dysprosium (Dy 3+ ) doped glasses of the potassium aluminum gadolinium phosphate (KAGP) were fabricated by melt-quenching technique. The preparation of glasses was varied the concentrations of Dy2 O3 at 0.00, 0.05, 0.10, 0.50, 1.00 and 3.00 mol%. The physical and spectroscopic properties were investigated for white light emitting devices. The absorption spectra were attributed to Dy 3+ transitions from the 6 H15/2, ground state to the various excited states and found that the intensity of absorption spectra was increased with increasing Dy2 O3 concentration. The Judd-Ofelt (JO) intensity parameter Ωλ (λ = 2, 4 and 6) were estimated from the absorption spectra of 0.50 mol% Dy2 O3 doped KAGP glass and found to be Ω2  > Ω4  > Ω6 . The photoluminescence (PL) spectra were record under 350 nm and showed four intense peaks at 482, 573, 664 and 753 nm which correspond to the excited states ( 4 F9/2 ) to 6 H15/2, 6 H13/2, 6 H11/2 and 6 H9/2 respectively. The intensity of emission spectra increased with content of Dy 3+ ions until 0.5 mol% in KAGP glasses and beyond concentration quenching was observed. From the emission spectra have evaluated chromaticity co-ordinates CIE 1931 and observed that the emission of KAGP glasses was in the white region. The results approve that the Dy 3+ doped KAGP glasses could be considered for optoelectronic devices such as lasers and white light emitting diode (w-LEDs). The radioluminescence (RL) spectra were measured and show the strongest emission from X-rays excitation at 0.5 mol% of Dy2 O3 . In evaluation of scintillation property between 0.50 mol% of Dy2 O3 doped KAGP glass and BGO crystal, the integral scintillation efficiency was 9% of BGO. It can be potential for integration mode of scintillation such as in medical and industrial X-ray imaging applications. Highlights: Dy 3+ doped glasses were fabricated. Emission at 482, 573, 664 and 753 nm were observed. Highest emission intensity is 0.5 mol% of Dy2 O3 . Best integral scintillation efficiency is 9% of BGO crystal.